Efektivitas Flip Chart Dan Media Audiovisual Terhadap Peningkatan Pengetahuan Siswa SD Negeri Katangka tentang Karies gigi - Rini Irmayanti Sitanaya (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Dental caries is a pathological process in the form of a process of damage that is limited to the hard tissue of the teeth that starts from the enamel and continues to the dentine. Primary children are the group most vulnerable to dental caries. One way to change behavior is to intervene in the way of providing information to improve the knowledge of elementary school students. Giving information to students will be more effective and optimal when using media or tools. Flipcharts and audiovisual media. Purpose: the purpose of this study is to know the comparison of the effectiveness of flipcharts and audiovisual media to increase the knowledge of students in the field of dental caries. methods: this research method is a quasi experiment with a non-equivalent control group design with previous and subsequent testing. Conclusion: the results of this study indicate that the provision of information on dental caries using flip chart media p = 0, .001 (p <0.005) and audiovisual media p = 0.004 (p <0.005). The results of the statistical test averaged the difference in the information on dental caries using the flipchart 15.25 media while using audiovisual media that was 17.75.